Act like a lady, think like a man : what men really think about love, relationships, intimacy, and commitment - Harvey, Steve, 1956-; Millner, Denene (New York : Amistad, 2009)
"From the host of the popular 'Steve Harvey morning show' comes a funny, honest, and foolproof guide for all women that takes them inside the heads of men and shows how men think about love, sex, and commitment"--Publisher.
Introduction: everything you need to know about men and relationships is right here -- The mind-set of a man. What drives men ; Our love isn't like your love ; The three things every man needs: support, loyalty, and the cookie ; "We need to talk", and other words that make men run for cover -- Why men do what they do. First things first: he wants to sleep with you ; Sports fish vs. keepers: how men distinguish between the marrying types and the playthings ; Mama's boys ; Why men cheat -- The playbook: how to win the game. Men respect standards-- get some ; The five questions every woman should ask before she gets in too deep ; The ninety-day rule: getting the respect you deserve ; If he's meeting the kids after you decide he's "the One," it's too late ; Strong, independent-- and lonely-- women ; How to get the ring ; Quick answers to the questions you've always wanted to ask.
Keywords: Mate selection